An evaluation of the speech perception in noise test - Lucille P. Dickens; Callum M. Delaney (South African Journal of Communication Disorders, 1986)
The effects of presentation level and signal-to-babble ratio (S/B) on SPIN performance were investigated for eighty normal hearing listeners. Both intensity and S/B had a significant effect on scores. Performance improved at the more favourable S/B regardless of presentation level, and scores were better at the lower presentation level regardless of S/B. Possible clinical applications of the SPIN test are discussed.